Gambaran kematangan emosi mahasiswi penggemar KPOP di Jakarta - Fitriyani Nurhasanah; Melina Lestari (Indonesian Counselor Association (IKI), 2024)
Emotional maturity affects an individual's ability to solve problems objectively. So female students who have good emotional control will find it easier to make life decisions, one of which is becoming a kpop fan, who still knows the priorities of individual life. The purpose of this study is to be able to find out the picture of the emotional maturity of female students who are kpop fans in one of the private high schools in Jakarta. This study uses a qualitative approach with a narrative method, by conducting semi-structured interviews with 9 female students. The data analysis technique uses Nvivo 14 with Word cloud and Project map features. The results of the study are that kpop fans have reached emotional maturity by showing the development of independence, being able to accept reality, being able to adapt well, how to respond appropriately, having emotional balance, having a sense of empathy and being able to control anger.